Collagenase From Vibrio alginolyticus Cultures: Experimental Study and Clinical Perspectives. (December 2016) - Bassetto, Franco; Maschio, Nicola; Abatangelo, Giovanni; Zavan, Barbara; Scarpa, Carlotta; Vindigni, Vincenzo
Purpose . The purpose of this study is to examine the activity of collagenase from cultures of Vibrio alginolyticus as in vitro as in biological samples and to evaluate clinical perspectives of this product about the treatment of fibroproliferative diseases like Dupuytren's contracture. Methods . The experimental part of the study has been divided in 2 stages. In the first stage, the collagenase has been produced in laboratory, assessing its purity, verifying the in vitro degradation of collagen by the enzyme and measuring the size of the fragments; in the second part, an experimental injection into samples of fibrous cord typical of Dupuytren's disease has been performed in vitro. For the injection we used only collagenase, or collagenase after having subjected them to 2 types of mechanical stress or a collagenase combined with ethylenediamine tetra-acetic acid. Considering that the human samples have been treated in vitro, our institution does not require a specific informed consent. Results . It appeared evident that the collagenase obtained from Vibrio alginolyticus (nonpathogenic bacterium) is highly pure (>98%) and does not contain nonspecific protease. The collagenase from Vibrio alginolyticus therefore has an excellent degradative capacity against the collagen and this activity takes on a dose- and time-dependent behavior. The collagenase from Vibrio alginolyticus does not act negatively on cell survival and collagen peptides obtained may provide a better proliferative stimulus compared to controls. Conclusions . The collagenase from Vibrio alginolyticus, given its obvious ability in vitro and biological samples, could be an option in the nonsurgical treatment of Dupuytren's disease. Level of evidence . Level III, therapeutic.